LENTIL YIELD AS INFLUENCED BY DENSITY OF WHEAT INTERCROPPING - Khaliq, A.; Khan, M. Bismillah; Saleem, M. Farrukh; Zamir, S. I. (Journal of Research (Science), 2001)
Studies on agro-economic relationship of component crops in a lentilwheat intercropping systems were conducted at the Agronomic Research Area, University of Agriculture, Faisalabad during the year 1996-97. Intercropping systems included lentil alone, lentil + one row of wheat, lentil + two rows of wheat, lentil + three rows of wheat, lentil + four rows of wheat and lentil alone. Lentil alone and wheat alone produced their maximum respective grain yields of 10.99 and 42.10 q ha-1 as compared to those recorded in various intercropping systems. While in terms of monetary gain, the highest net income of Rs.21680.13 ha-1 was obtained from an intercropping system of lentil + two rows of wheat as against the lowest of Rs. 10819.28 ha-1 in case of wheat alone.